Exogenous 8-hydroxydeoxyguanosine attenuates doxorubicin-induced cardiotoxicity by decreasing pyroptosis in H9c2 cardiomyocytes - Soyoung Hwang; Se-Hee Kim; Kwai Han Yoo; Myung-Hee Chung; Jin Woo Lee; Kuk Hui Son (BMC Molecular and Cell Biology, 2022)
Abstract Doxorubicin (DOX), which is widely used in cancer treatment, can induce cardiomyopathy. One of the main mechanisms whereby DOX induces cardiotoxicity involves pyroptosis through the NLR family pyrin domain containing 3 (NLRP3) inflammasome and gasdermin D (GSDMD). Increased NAPDH oxidase (NOX) and oxidative stress trigger pyroptosis. Exogenous 8-hydroxydeoxyguanosine (8-OHdG) decreases reactive oxygen species (ROS) production by inactivating NOX. Here, we examined whether 8-OHdG treatment can attenuate DOX-induced pyroptosis in H9c2 cardiomyocytes. Exposure to DOX increased the peroxidative glutathione redox status and NOX1/2/4, toll-like receptor (TLR)2/4, and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) expression, while an additional 8-OHdG treatment attenuated these effects. Furthermore, DOX induced higher expression of NLRP3 inflammasome components, including NLRP3, apoptosis-associated speck-like protein containing a c-terminal caspase recruitment domain (ASC), and pro-caspase-1. Moreover, it increased caspase-1 activity, a marker of pyroptosis, and interleukin (IL)-1β expression. All these effects were attenuated by 8-OHdG treatment. In addition, the expression of the cardiotoxicity markers, atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) was increased by DOX, whereas the increase of ANP and BNP induced by DOX treatment was reversed by 8-OHdG. In conclusion, exogenous 8-OHdG attenuated DOX-induced pyroptosis by decreasing the expression of NOX1/2/3, TLR2/4, and NF-κB. Thus, 8-OHdG may attenuate DOX-induced cardiotoxicity through the inhibition of pyroptosis.